SECTIONAL CURVATURE DUCTILTY OF REINFORECD CONCRETE COLUMNS UNDER LARGE INELASTIC DEFORMATION - Raad K. Al-Azzawi (Journal of Engineering, 2024)
A mathematical model is developed to express stress-strain relationship of normal-strength concrete confined by transverse reinforcement. The sectional ductility analysis on rectangular reinforced concrete columns is performed under axial load. Analytical modals available in the literatures for confinement concrete by different types of transverse reinforcement are used. A parametric study is performed to study the influence of these parameters on the curvature ductility of reinforced concrete columns. The main parameters introduced are the amount of longitudinal reinforcement, amount of transverse reinforcement, tie spacing and the level of the compression axial force. The experimental and analytical results available in the literatures are being compared with present study.